2016
DOI: 10.3390/molecules22010064
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Antibacterial Evaluation of New Sulfone Derivatives Containing 2-Aroxymethyl-1,3,4-Oxadiazole/Thiadiazole Moiety

Abstract: Sulfones are one of the most important classes of agricultural fungicides. To discover new lead compounds with high antibacterial activity, a series of new sulfone derivatives were designed and synthesized by introducing the aroxymethyl moiety into the scaffold of 1,3,4-oxadiazole/thiadiazole sulfones. Antibacterial activities against three phytopathogens (Xanthomonas oryzae pv. oryzae, Ralstonia solanacearum, Xanthomonas axonopodis pv. citri.) were assayed in vitro. As compared to the control of commercial fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
36
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 36 publications
(40 citation statements)
references
References 25 publications
1
36
0
1
Order By: Relevance
“…51 When the thioether group at the 2-position of 1,3,4-oxadiazole ring was replaced with sulfone group, and when the thioether group at the 5-position of 1,3,4-oxadiazole ring was replaced with oxygen ether, phenyl or benzyl group, the in vitro antibacterial activities of the corresponding compounds were lower (phenyl group) or better (oxygen ether and benzyl group) than those of the target compounds. 9,[11][12][13] Therefore, the SAR analysis demonstrated that both thioether groups at the 2,5-positions of 1,3,4-oxadiazole ring play a significant role in the design of the target compounds.…”
Section: Structure-activity Relationship Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…51 When the thioether group at the 2-position of 1,3,4-oxadiazole ring was replaced with sulfone group, and when the thioether group at the 5-position of 1,3,4-oxadiazole ring was replaced with oxygen ether, phenyl or benzyl group, the in vitro antibacterial activities of the corresponding compounds were lower (phenyl group) or better (oxygen ether and benzyl group) than those of the target compounds. 9,[11][12][13] Therefore, the SAR analysis demonstrated that both thioether groups at the 2,5-positions of 1,3,4-oxadiazole ring play a significant role in the design of the target compounds.…”
Section: Structure-activity Relationship Analysismentioning
confidence: 99%
“…It has recently been shown that the 1,3,4-oxadiazole ring, one of the most important and well-known heterocyclic nuclei, exhibits a wide variety of pesticidal biological activities, including antibacterial, [7][8][9][10][11][12][13] antifungal, [14][15][16][17][18][19][20][21] antiviral, [21][22][23] insecticidal, [24][25][26][27] and herbicidal. 28,29 In addition, in 2005, Guimarães et al demonstrated that introduction of a 1,3,4-oxadiazole ring into target compounds could change their polarity, flexibility and metabolic stability, effectively enhancing their bioactivity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Otherwise, N‐heteroaromatic compounds such as indole are also valorized in the synthesis of fine chemical (pharmaceuticals, agrochemicals, and dyes) . These reactions are conventionally performed over both liquid phase Brønsted acids and Lewis acids .…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have shown that two or three heterogeneous atoms such as nitrogen and sulfur are expected to have antimicrobial activities . In addition, many 1,3,4‐thiadiazoles are used as fungicides, bactericides, and herbicides in the agricultural field . Acid hydrazides are reactive substances and have been used as useful synthons of various heterocyclic rings with one or several heteroatoms.…”
Section: Introductionmentioning
confidence: 99%